Iron Status, Prevalence and Risk Factors of Iron Deficiency Anemia Among 12- to 15-Year-Old Adolescent Girls from Different Socioeconomic Status in Indonesia - Sumarlan, Eka S; Windiastuti, Endang; Gunardi, Hartono (Makara Journal of Health Research, 2018)
Background: The aim of this study was to determine the iron status and the prevalence and risk factors of iron deficiency anemia (IDA) among adolescent girls in Central Jakarta, Indonesia. Methods: A cross-sectional study was conducted among 12- to 15-year-old girls studying in junior high schools that were categorized into high and low socioeconomic status (SES). Their menstrual and nutritional status, parents’ education level and income, and iron intake were assessed. Tuberculin test and assessments for C-reactive protein levels and hematologic and iron parameters were also conducted. Results: Iron status was normal in 69.3% of 163 subjects. The prevalence of non-anemic iron deficiency was higher (17.2%; 3.1% iron depletion and 14.1% iron deficiency) than that of IDA (13.5%). The prevalence of IDA was lower among girls from the high SES than that among girls from the low SES (11.5% and 15.8%, respectively). There was no significant relationship among IDA and nutritional status, menstrual status and characteristics, SES, iron intake, and parents’ education level and income; however, bioavailable iron intake in all subjects was found to be less compared to the recommended daily allowance (RDA). Conclusions: The higher prevalence of non-anemic iron deficiency than IDA is a potential risk factor for increasing the prevalence of IDA in the future. No significant relationship was found between IDA and its risk factors; however, iron intake was less compared to the RDA in all subjects, which requires further attention.